A3B4 type magnesium-containing C14 structure Laves phase room temperature reversible hydrogen storage high entropy alloy and preparation method thereof
By designing the A3B4 type magnesium-containing C14 structure Laves phase high-entropy alloy, the problems of difficulty in controlling components and insufficient hydrogen storage performance in the preparation process of traditional magnesium-containing high-entropy alloys are solved, and the preparation of high-purity alloys and good hydrogen storage performance are achieved.
Patent Information
- Application Number
- CN202310503010.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-06
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-05-06
AI Technical Summary
In the prior art, magnesium-containing high-entropy alloys have problems such as difficult to control the components during the preparation process, the alloy consists of a multiphase, the high hydrogen release temperature, and the difficulty in preparing high-purity Laves, which limits the improvement of its hydrogen storage performance.
A A3B4 type magnesium-containing C14 structure Laves phase room temperature reversible hydrogen storage high entropy alloy was designed, and an arc smelting, mechanical crushing and wet ball milling of Mg powder were prepared by step-by-step sintering method.
The preparation of a high-purity A3B4 magnesium-containing C14 structure Laves phase high-entropy alloy has a room temperature hydrogen storage capacity of 0.7 to 0.9 wt.% and a room temperature rapid reversible hydrogen storage performance, reducing the cost and density of the alloy.
Smart Images

Figure CN116555657B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrogen storage materials and specifically relates to a 3 B 4 A type magnesium-containing C14 structure Laves phase room temperature reversible hydrogen storage high entropy alloy and a preparation method thereof. Background Art
[0002] At present, human life is extremely dependent on fossil fuels, which has led to environmental pollution, global warming and energy crisis. Therefore, it is extremely important to develop and utilize clean and efficient renewable energy. Nowadays, hydrogen energy has been widely studied because of its clean, efficient, zero-carbon and sustainable characteristics, but its development and utilization still needs to solve the problem of hydrogen storage.
[0003] Compared with gaseous hydrogen storage and liquid hydrogen storage, solid hydrogen storage is widely used due to its higher energy density and safety. According to the different atomic ratios of the A (hydride-forming element) and B (hydrogen-weak affinity element) sides of the hydrogen storage alloy, the hydrogen storage alloys currently developed include AB type (TiFe), AB 2 Type (YMgNi 4 ), AB 3 Type (Sm 2 MgNi 9 ), AB 5 Type (LaNi 5 ) and A 2 Type B (Mg 2 However, the low hydrogen storage density still limits the application and development of these alloys. Therefore, it is of great significance to explore new high-density hydrogen storage alloys.
[0004] High entropy alloys are considered to be very ideal hydrogen storage alloys. On the one hand, high entropy alloys are composed of multiple elements. The difference in atomic half-valence makes high entropy alloys have more lattice gaps, defects and strains, thereby providing more vacancies and channels, which are conducive to the diffusion, dissociation and recombination of hydrogen atoms; on the other hand, high entropy alloys are composed of multiple metal elements with different electronegativity or valence electrons, which is conducive to regulating metal-metal and metal-hydrogen interactions, thereby weakening the corresponding bond energy and promoting the rapid migration of hydrogen atoms. In addition, the use of multiple elements greatly increases the possibility of developing material combinations with excellent hydrogen storage performance. Therefore, the emergence of high entropy alloys provides new opportunities for improving the hydrogen storage performance of alloys.
[0005] Nowadays, intermetallic high entropy alloys containing Laves phase have attracted much attention due to their high hydrogen storage capacity and good low-temperature reversible hydrogen storage performance. 2The AB-type TiZrFeMnCrV high entropy alloy still has a hydrogen storage capacity of about 1.76wt.% after 50 cycles [J Chen, Z Li, H Huang, et al. Scripta Materialia, 2022, 212: 114548.]; at 473K, the AB-type TiZrNbCrFeNi high entropy alloy with C14 Laves phase can obtain a reversible hydrogen storage capacity of 1.1wt.% [G Andrade, G Zepon, K Edalat, et al. International Journal of Hydrogen Energy, 2023.], and the A-type TiZrNbCrFeNi high entropy alloy with C14 Laves phase as the main phase can obtain a reversible hydrogen storage capacity of 1.1wt.%. 3 B 2 Type TiZrNbCrFe high entropy alloy even has a reversible hydrogen storage capacity of 1.9wt.% [R Floriano, G Zepon, K Edalati, et al. International Journal of Hydrogen Energy, 2021, 46(46): 23757-23766.]. This has inspired people to explore new structural high entropy hydrogen storage alloys. Since regulating the A / B ratio can change the atomic proportions and atomic occupancy in the unit cell, thereby achieving the effect of regulating the chemical environment of the tetrahedral gap and the unit cell volume, it can ultimately effectively regulate the hydrogen storage capacity, hydrogen absorption and desorption kinetics, and hydrogen absorption and desorption platform of the alloy. Hydrogen storage properties; therefore, designing different A / B type intermetallic high entropy alloys and adding light elements to the alloy have the potential to further improve the hydrogen storage performance of the alloy. For example, relative to AB 2 For hydrogen storage alloys, when A / B>1 / 2 in the alloy, the following three situations will occur: (1) A vacancy appears at the position occupied by the atom on the B side, forming AB 2-x (2) Some of the atoms on the A side occupy the positions of the atoms on the B side, forming an A 1+x / 3 B 2 A 2x / 3 alloy; (3) precipitation of a new second phase, causing the actual main phase composition to deviate from the design value. The occurrence of these situations may improve the hydrogen storage performance of the alloy, such as hydrogen storage capacity and cycle stability. In addition, compared with transition metal elements, metallic Mg has the advantages of high hydrogen storage capacity, low density, wide source and low cost. Adding Mg to Laves phase intermetallic high entropy alloys can better reduce the density of the alloy and have the possibility of further improving the hydrogen storage capacity.
[0006] However, there are few reports on magnesium-containing C14 structure Laves phase hydrogen storage high entropy alloys in domestic and foreign literature. This is mainly attributed to the many difficulties in the preparation of magnesium-containing alloys: first, due to the large difference in the melting point and boiling point between Mg and transition metal elements such as Zr and V, a large amount of Mg is easily volatilized during the smelting process, which is not conducive to the precise control of the composition of magnesium-containing high entropy alloys on the one hand, and unsafe in production on the other hand; secondly, mechanical alloying is currently a common method for preparing magnesium-containing high entropy alloys, but the preparation of magnesium-containing high entropy alloys using this method not only requires a long ball milling time, which leads to the risk of contamination and oxidation of the alloy, but also the prepared magnesium-containing high entropy alloys are mostly composed of multiple phases and have a high hydrogen desorption temperature (generally at 300°C for rapid hydrogen desorption); in addition, it is difficult to prepare high-purity Laves phase magnesium-containing hydrogen storage high entropy alloys using mechanical alloying, which leads to the deterioration of material properties.
[0007] In view of this, how to design and prepare a new type of A 3 B 4 This type of magnesium-containing C14 structure Laves phase room temperature reversible hydrogen storage high entropy alloy has important practical application value. Summary of the invention
[0008] The purpose of the present invention is to overcome the problems existing in the conventional technology and to design a new type of A 3 B 4 A type of magnesium-containing C14 Laves phase room temperature reversible hydrogen storage high entropy alloy was developed, and the corresponding preparation method was developed. 2 V 2- x Fe x CrNi (x = 0 ~ 1) alloy molecular formula is used to prepare the raw materials, and then the alloy precursor is prepared by arc melting; according to Zr 2 V T 2-x Fe x CrNi (x = 0 ~ 1) alloy molecular formula The mechanically crushed precursor and Mg powder were weighed and wet ball milled; then the ball milled sample was sintered step by step to obtain A 3 B 4 The present invention prepares a type of magnesium-containing C14 structure Laves phase room temperature reversible hydrogen storage high entropy alloy for the first time. 3 B 4 The new type of hydrogen storage high entropy alloy is mainly composed of high-purity C14 Laves phase, and the alloy does not contain rare earth elements. At the same time, the added Mg content is as high as 14%, which greatly reduces the cost and density of the alloy. In addition, the new type of A 3 B 4The magnesium-containing C14 Laves phase high entropy alloy has a hydrogen storage capacity of 0.7 to 0.9 wt.% (mass percentage) at room temperature, and has the characteristics of rapid reversible hydrogen storage at room temperature and easy activation.
[0009] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:
[0010] The present invention provides a 3 B 4 A type of magnesium-containing C14 structure Laves phase room temperature reversible hydrogen storage high entropy alloy, the chemical formula of which is Zr 2 V T 2-x Fe x CrNi, wherein x=0-1, A / B=3 / 4, the A-type elements include Zr and Mg, and the B-type elements include V, Fe, Cr and Ni.
[0011] The present invention also provides a 3 B 4 The method for preparing a room temperature reversible hydrogen storage high entropy alloy with a C14 structure Laves phase containing magnesium comprises the following steps:
[0012] 1) Press Zr first 2 V 2-x Fe x CrNi alloy molecular formula Weigh a certain amount of zirconium block, vanadium block, iron block, nickel sheet and chromium sheet; in an argon atmosphere, spread the above metal raw materials from bottom to top in the crucible according to the melting point from low to high, and then -2 The alloy is completely melted and cooled to form an alloy ingot. The alloy ingot is turned over and repeatedly melted 3 to 4 times to obtain a precursor sample of a hydrogen storage high entropy alloy.
[0013] 2) In a glove box, the obtained precursor sample was mechanically crushed into a precursor powder of 100-300 mesh using a stainless steel mortar;
[0014] 3) Press Zr 2 V T 2-x Fe x CrNi alloy molecular formula Precursor powder and Mg powder were weighed, and the weighed metal powders were poured into a ball milling jar in a glove box, and ball milled to obtain a ball milled sample;
[0015] 4) Weigh a certain amount of the ball-milled sample using an analytical balance in a glove box, and press it into tablets with a diameter of 10 to 15 mm using a powder tablet press;
[0016] 5) Place the pressed tablet in a stainless steel sealed container in a glove box and fill it with argon gas at a pressure of 0.2-0.4 MPa; then place it in an annealing furnace for step-by-step sintering, and after sintering, cool it to room temperature and take it out to finally obtain A 3 B 4 Type magnesium-containing C14 structure Laves phase room temperature reversible hydrogen storage high entropy alloy.
[0017] Furthermore, in step 1), the purity of the zirconium block is ≥99.7%, the purity of the vanadium block is ≥99.9%, the purity of the iron block is ≥99.9%, the purity of the nickel sheet is ≥99.5%, and the purity of the chromium sheet is ≥99.5%; in step 3), the purity of the Mg powder is ≥99.5%.
[0018] Furthermore, in step 3), the specific operation of ball milling is as follows: grinding steel balls are added at a ball-to-material ratio of 40:1, and then n-heptane is poured into the grinding balls to cover them, and then the ball mill jar is sealed and placed on a planetary ball mill for wet milling for 3 to 5 hours. The speed of the ball mill is 300 to 400 rpm, and the ball mill is stopped for 5 minutes after each 30 minutes of wet milling.
[0019] Furthermore, the cover of the ball mill was removed in the glove box, the n-heptane above the powder was extracted with a rubber-tipped dropper, and the ball mill was placed in a transition chamber and vacuumed for 1 to 2 hours.
[0020] Furthermore, in step 3), 20 wt.% of Mg powder is additionally added to compensate for the burning loss of Mg powder in the subsequent sintering process.
[0021] Furthermore, in step 5), the step-by-step sintering is divided into three stages: the first stage is to keep warm at 450°C for 3 hours, the second stage is to keep warm at 750°C for 3 hours, and the third stage is to keep warm at 850°C for 4 hours.
[0022] The present invention also provides the above-mentioned A 3 B 4 The application of magnesium-containing C14 structure Laves phase room temperature reversible hydrogen storage high entropy alloy in hydrogen storage. Before utilizing the hydrogen storage function of the high entropy alloy, it is subjected to 2 to 3 cycles of hydrogen absorption and desorption at 350°C and 3.5MPa to obtain the activity of the hydrogen storage high entropy alloy, which can then be used for hydrogen storage.
[0023] The principle of the present invention is: in the newly designed Zr 2 V 2-x Fe x On the basis of CrNi (x = 0 ~ 1) alloy, the hydrogen storage performance of the alloy is improved by adding Mg, which can be attributed to the following two aspects: on the one hand, the addition of the light element Mg significantly reduces the density of the alloy, thereby increasing the hydrogen storage capacity of the alloy; on the other hand, the addition of Mg changes the stoichiometric ratio of the alloy, thus forming a new type of A3 B 4 Type hydrogen storage alloy. Vacancies appear at the positions occupied by the B-side atoms in the alloy, and are occupied by some A-side atoms, resulting in the alloy producing defect structures such as dislocations, twins and stacking faults that are beneficial to the diffusion of hydrogen and the nucleation and growth of hydrides, which is beneficial to improving the hydrogen absorption and desorption kinetics and hydrogen storage capacity of the alloy. In addition, the hydrogen storage high entropy alloy designed by the present invention has a high-purity C14 Laves phase as the main phase, which makes the alloy have better hydrogen storage performance: on the one hand, this is because the Laves phase crystal structure has higher hydrogen storage capacity and low-temperature reversible hydrogen storage characteristics; on the other hand, due to the difference in atomic radius and electronegativity, the high entropy alloy has more lattice gaps, defects and strains, while weakening the bond energy between the alloy and hydrogen atoms, promoting the diffusion, dissociation and recombination of hydrogen atoms.
[0024] Compared with the prior art, the beneficial technical effects of the present invention are as follows:
[0025] 1. The present invention first designs a new A 3 B 4 A type of magnesium-containing C14 Laves phase room temperature reversible hydrogen storage high entropy alloy was prepared, and a corresponding preparation method was developed. The preparation method is simple and easy to control, which overcomes the problems of difficult control of the composition of magnesium-containing high entropy alloys during the preparation process and the alloys being composed of multiple phases. It can accurately control the composition and phase purity of magnesium-containing high entropy alloys, and finally accurately prepare A with high-purity C14 Laves phase as the main phase. 3 B 4 Type magnesium-containing hydrogen storage high entropy alloy.
[0026] 2. The present invention successfully prepared a 3 B 4 Type magnesium-containing C14 structure Laves phase room temperature reversible hydrogen storage high entropy alloy, Zr 2 V T 2-x Fe x CrNi (x=0-1) alloy does not contain rare earth elements, and the added Mg content can reach 14%, which greatly reduces the cost and density of the alloy.
[0027] 3. Zr prepared by the present invention 2 V T 2-x Fe x CrNi high entropy alloy is easy to activate and can be fully activated by absorbing and releasing hydrogen 2 to 3 times at 350°C.
[0028] 4. Zr prepared by the present invention 2 V T 2-x Fe xCrNi high entropy alloy has the characteristics of rapid and reversible hydrogen storage at room temperature. It has a hydrogen storage capacity of 0.7 to 0.9 wt.% (mass percentage) at room temperature and has good prospects for hydrogen storage applications.
[0029] Of course, any product implementing the present invention does not necessarily need to achieve all of the above advantages at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0031] Figure 1 It is the X-ray diffraction (XRD) test spectra of the high entropy alloy sample before hydrogen absorption, sample after hydrogen absorption and sample after hydrogen release;
[0032] in, Figure 1 (a) is Zr 2 V T 2 CrNi high entropy alloy; Figure 1 (b) Zr 2 MgVFeCrNi high entropy alloy;
[0033] Figure 2 Zr 2 V T 2 CrNi and Zr 2 Isothermal hydrogen absorption kinetics curve of MgVFeCrNi high entropy alloy at 303K;
[0034] Figure 3 It is the constant temperature hydrogen release kinetic curve of high entropy alloy at different temperatures;
[0035] in, Figure 3 (a) is Zr 2 V T 2 CrNi high entropy alloy; Figure 3 (b) Zr 2 MgVFeCrNi high entropy alloy. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The present invention provides A 3 B 4 The room temperature reversible hydrogen storage high entropy alloy with C14 structure Laves phase containing magnesium is Zr 2 V T 2-x Fe x CrNi (x = 0 to 1). 2 V 2-x Fe x A is obtained by melting the CrNi (x = 0-1) precursor, wet ball milling the precursor and Mg, and step-by-step sintering of the ball milled sample. 3 B 4 A type of room temperature reversible hydrogen storage high entropy alloy containing C14 structure Laves phase of magnesium. The preparation method is simple and the process is easy to control. It can overcome the problems that the composition of magnesium-containing alloys is difficult to control during the preparation process and the alloys are composed of multiple phases, and can accurately control the composition and phase purity of magnesium-containing high entropy alloys. The hydrogen storage high entropy alloy prepared by the present invention does not contain rare earth elements, and the content of lightweight Mg elements is as high as 14%, which greatly reduces the cost and density of the alloy; the hydrogen storage high entropy alloy has a hydrogen storage capacity of 0.7 to 0.9wt.% (mass percentage) at room temperature. Compared with other high entropy alloys, the material provided by the present invention has the excellent properties of easy activation and reversible hydrogen absorption and desorption at room temperature.
[0038] The relevant specific embodiments of the present invention are:
[0039] Example 1
[0040] Zr 2 V T 2 The specific preparation steps of CrNi high entropy alloy are as follows:
[0041] (1) Press Zr first 2 V 2 CrNi alloy molecular formula Weigh a certain amount of zirconium block (purity ≥ 99.7%), vanadium block (purity ≥ 99.9%), nickel sheet (purity ≥ 99.5%) and chromium sheet (purity ≥ 99.5%), the total mass of the alloy is 30g; in an argon atmosphere, the above metal raw materials are laid from bottom to top in a crucible according to the melting point from low to high, and then arc vacuum melting (vacuum degree is 3×10 -3 Pa), the alloy is completely melted and cooled to form an alloy ingot, the alloy ingot is turned over and smelted repeatedly for 4 times to obtain Zr 2 V 2 CrNi precursor;
[0042] (2) In a glove box, the precursor was mechanically crushed into 200 mesh powder using a stainless steel mortar;
[0043] (3) Press Zr 2 V T2 CrNi alloy molecular formula Weigh the precursor powder and Mg powder (purity ≥ 99.5%), and consider a certain amount of Mg burn-out rate (20wt.%). Then pour the weighed metal powder into a ball mill in a glove box, add grinding steel balls at a ball-to-material ratio of 40:1, and then pour n-heptane (purity ≥ 99%) to cover the grinding balls, and then seal the ball mill and place it on a planetary ball mill for wet grinding for 5 hours. The speed of the ball mill is 400rpm, and the ball mill stops working for 5 minutes after every 30 minutes of wet grinding. Then remove the cover of the ball mill in the glove box, use a rubber-tipped dropper to extract the n-heptane above the powder, and then place the ball mill in a transition bin and evacuate for 2 hours to obtain a ball-milled sample;
[0044] (4) Weigh 20 g of the ball-milled sample using an analytical balance in a glove box and press it into a tablet with a diameter of 13 mm using a powder tablet press;
[0045] (5) Place the pressed tablet in a stainless steel sealed container in a glove box and fill it with argon gas at a pressure of 0.4 MPa; then place it in an annealing furnace for step-by-step sintering, namely: keep the temperature at 450°C, 750°C and 850°C for 3 h, 3 h and 4 h respectively, with a heating rate of 5°C / min. After sintering, cool it to room temperature and take it out to finally obtain Zr 2 V T 2 CrNi high entropy alloy.
[0046] Zr 2 V T 2 The CrNi high entropy alloy is composed of C14 Laves / C15 Laves dual phases. Phase fitting shows that the content of C14 Laves phase in the alloy is as high as 88wt.%. After complete hydrogen absorption, both Laves phases absorb hydrogen, causing their X-ray diffraction peaks to shift to the left (see Figure 1 (a): Zr 2 V T 2 X-ray diffraction (XRD) test spectra of CrNi high entropy alloy, hydrogen absorption sample and hydrogen desorption sample). After the hydrogen is completely desorbed, the diffraction peaks corresponding to the two Laves phases in the alloy return to their original positions, indicating that both Laves phases have completely desorbed hydrogen (see Figure 1 (a): Zr 2 V T 2 CrNi high entropy alloy, hydrogen absorption sample and hydrogen release sample X-ray diffraction (XRD) test spectrum), the alloy has the performance of reversible hydrogen storage. 2 V T 2 CrNi high entropy alloy can absorb 0.8wt.% hydrogen at 303K (see Figure 2 :Zr 2 V T 2CrNi high entropy alloy isothermal hydrogen absorption kinetics curve at 303K), and releases about 0.3wt.% hydrogen at 303K, while completely releasing hydrogen at 523K, with a maximum hydrogen release capacity of about 0.7wt.% (see Figure 3 (a): Zr 2 V T 2 Isothermal hydrogen desorption kinetics curve of CrNi high entropy alloy at different temperatures).
[0047] Example 2
[0048] Zr 2 The specific preparation steps of MgVFeCrNi high entropy alloy are as follows:
[0049] (1) Press Zr first 2 VFeCrNi alloy formula Weigh a certain amount of zirconium block (purity ≥ 99.7%), vanadium block (purity ≥ 99.9%), iron block (purity ≥ 99.9%), nickel sheet (purity ≥ 99.5%) and chromium sheet (purity ≥ 99.5%), the total mass of the alloy is 30g; in an argon atmosphere, lay the above metal raw materials from bottom to top in the crucible according to the melting point from low to high, and then perform arc vacuum melting (vacuum degree of 3×10 -3 Pa), the alloy is completely melted and cooled to form an alloy ingot, the alloy ingot is turned over and smelted repeatedly for 4 times to obtain Zr 2 VFeCrNi precursor;
[0050] (2) In a glove box, the precursor was mechanically crushed into 200 mesh powder using a stainless steel mortar;
[0051] (3) Press Zr 2 MgVFeCrNi alloy molecular formula Weigh the precursor powder and Mg powder (purity ≥ 99.5%), and consider a certain amount of Mg burn-out rate (20wt.%). Then pour the weighed metal powder into a ball mill in a glove box, add grinding steel balls at a ball-to-material ratio of 40:1, and then pour n-heptane (purity ≥ 99%) to cover the grinding balls, and then seal the ball mill and place it on a planetary ball mill for wet grinding for 5 hours. The speed of the ball mill is 400rpm, and the ball mill stops working for 5 minutes after every 30 minutes of wet grinding. Then remove the cover of the ball mill in the glove box, use a rubber-tipped dropper to extract the n-heptane above the powder, and then place the ball mill in a transition bin and evacuate for 2 hours to obtain a ball-milled sample;
[0052] (4) Weigh 20 g of the ball-milled sample using an analytical balance in a glove box and press it into a tablet with a diameter of 13 mm using a powder tablet press;
[0053] (5) Place the pressed tablet in a stainless steel sealed container in a glove box and fill it with argon gas at a pressure of 0.4 MPa; then place it in an annealing furnace for step-by-step sintering, namely: keep the temperature at 450, 750 and 850 °C for 3, 3 and 4 h respectively, with a heating rate of 5 °C / min. After sintering, cool it to room temperature and take it out to finally obtain Zr 2 MgVFeCrNi high entropy alloy.
[0054] Zr 2 MgVFeCrNi high entropy alloy consists of C14 Laves single phase. After complete hydrogen absorption, the C14 Laves phase absorbs hydrogen, causing its X-ray diffraction peak to shift to the left (see Figure 1 (b):Zr 2 X-ray diffraction (XRD) test spectra of MgVFeCrNi high entropy alloy, hydrogen absorption sample and hydrogen desorption sample). After the hydrogen is completely desorbed, the diffraction peak corresponding to the C14 Laves phase in the alloy returns to its original position, indicating that the hydrogen is completely desorbed from the C14 Laves phase (see Figure 1 (b):Zr 2 MgVFeCrNi high entropy alloy, hydrogen absorption sample and hydrogen release sample X-ray diffraction (XRD) test spectrum), the alloy has the performance of reversible hydrogen storage. Zr 2 MgVFeCrNi high entropy alloy can absorb 0.9wt.% hydrogen at 303K (see Figure 2 :Zr 2 The isothermal hydrogen absorption kinetics of MgVFeCrNi high entropy alloy at 303K) releases about 0.5wt.% hydrogen at 303K and completely releases hydrogen at 523K (see Figure 3 (b):Zr 2 Isothermal hydrogen desorption kinetics curve of MgVFeCrNi high entropy alloy at different temperatures).
[0055] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A room temperature reversible hydrogen storage high entropy alloy of A3B4 type magnesium-containing C14 structure Laves phase, characterized in that: The chemical formula of this material is Zr2MgV 2-x Fe x CrNi, wherein x=0-1, A / B=3 / 4, the A-type elements include Zr and Mg, and the B-type elements include V, Fe, Cr and Ni.
2. The method for preparing the A3B4 type magnesium-containing C14 structure Laves phase room temperature reversible hydrogen storage high entropy alloy according to claim 1, characterized in that: The steps include: 1) Press Zr2V first 2-x Fe x CrNi alloy molecular formula Weigh a certain amount of zirconium block, vanadium block, iron block, nickel sheet and chromium sheet; in an argon atmosphere, spread the above metal raw materials from bottom to top in the crucible according to the melting point from low to high, and then -2 The alloy is completely melted and cooled to form an alloy ingot. The alloy ingot is turned over and repeatedly melted 3 to 4 times to obtain a precursor sample of a hydrogen storage high entropy alloy. 2) In a glove box, the obtained precursor sample was mechanically crushed into a precursor powder of 100-300 mesh using a stainless steel mortar; 3) According to Zr2MgV 2-x Fe x CrNi alloy molecular formula Precursor powder and Mg powder were weighed, and the weighed metal powders were poured into a ball milling jar in a glove box, and ball milled to obtain a ball milled sample; 4) Weigh a certain amount of the ball-milled sample using an analytical balance in a glove box, and press it into tablets with a diameter of 10 to 15 mm using a powder tablet press; 5) placing the pressed sheet in a stainless steel sealed container in a glove box and filling it with argon gas at a pressure of 0.2 to 0.4 MPa; then placing it in an annealing furnace for step-by-step sintering, and taking it out after cooling it to room temperature with the furnace after sintering, to finally obtain an A3B4 type magnesium-containing C14 structure Laves phase room temperature reversible hydrogen storage high entropy alloy.
3. The preparation method according to claim 2, characterized in that: In step 1), the purity of the zirconium block is ≥99.7%, the purity of the vanadium block is ≥99.9%, the purity of the iron block is ≥99.9%, the purity of the nickel sheet is ≥99.5%, and the purity of the chromium sheet is ≥99.5%; in step 3), the purity of the Mg powder is ≥99.5%.
4. The preparation method according to claim 2, characterized in that: In step 3), the specific operation of ball milling is as follows: grinding steel balls are added at a ball-to-material ratio of 40:1, and then n-heptane is poured into the grinding balls to cover them. The ball mill jar is sealed and placed on a planetary ball mill for wet milling for 3 to 5 hours. The speed of the ball mill is 300 to 400 rpm, and the ball mill is stopped for 5 minutes after each 30 minutes of wet milling.
5. The preparation method according to claim 4, characterized in that: Next, remove the cover of the ball mill in the glove box, use a rubber-tipped dropper to extract the n-heptane above the powder, and then place the ball mill in a transition chamber and evacuate the chamber for 1 to 2 hours.
6. The preparation method according to claim 2, characterized in that: In step 3), 20 wt.% of Mg powder is additionally added to compensate for the burning loss of Mg powder during the subsequent sintering process.
7. The preparation method according to claim 2, characterized in that: In step 5), the step sintering is divided into three stages: the first stage is to keep warm at 450°C for 3 hours, the second stage is to keep warm at 750°C for 3 hours, and the third stage is to keep warm at 850°C for 4 hours.
8. Application of the A3B4 type magnesium-containing C14 structure Laves phase room temperature reversible hydrogen storage high entropy alloy according to claim 1 in hydrogen storage, characterized in that: Before utilizing the hydrogen storage function of the high entropy alloy, hydrogen absorption and desorption are cycled 2 to 3 times at a temperature of 350°C and a pressure of 3.5MPa to obtain the activity of the hydrogen storage high entropy alloy, after which it can be used for hydrogen storage.
Citation Information
Patent Citations
High-entropy intermetallic compound
CN107475596A
Cobalt-iron-nickel-vanadium-zirconium eutectic high-entropy alloy and preparation method thereof
CN114836669A